The Blue Survey: Validation of an instrument to measure ocean literacy among adults - EVELYN PAREDES-CORAL; TIM DEPREZ; MELITA MOKOS; ANN VANREUSEL; HENK ROOSE (Mediterranean Marine Science, 2021)
Human activities have put the ocean under unprecedented pressure. Still, levels of public understanding about the ocean remain low. Ocean literacy is a global movement that aims to improve the understanding of the ocean and provide an incentive for positive change in people’s behavior. To date, there is no validated scale targeted to adults to measure ocean literacy that includes measuring people’s knowledge about the ocean, as well as surveying their attitudes and willingness to act. The Blue Survey is an online instrument meant to measure ocean literacy in adult populations developed by a multidisciplinary team of experts. Using factor analysis, we explore the validity and internal consistency of the Blue Survey in a purposive online sample of 251 adults. We found ocean literacy to consist of six sub-dimensions captured by 34 survey items, viz. knowledge of ocean-related topics, personal interest in ocean-related aspects, ocean stewardship, ocean as an economic resource, ocean-friendly behavior, and willingness to act responsibly for the ocean. Our analysis resulted in the development of a new validated instrument to measure the various dimensions of ocean literacy. It may help researchers and practitioners to better understand the factors contributing to shaping an ocean-literate person. Further research should assess the validity of the Blue Survey across different populations, including those closely related to the sea, such as maritime professionals.

Mapping Global Research on Ocean Literacy: Implications for Science, Policy, and the Blue Economy - Evelyn Paredes-Coral; Melita Mokos; Ann Vanreusel; Tim Deprez (Frontiers in Marine Science, 2021)
In recent years, ocean literacy has become a global movement that connects the human dimension to the ocean and intends to be an incentive for positive change in people’s behavior. As multiple initiatives on ocean literacy have arisen, a comprehensive understanding of this topic is required to better engage the broader society. In the present study, we applied a combination of bibliometric analysis and science mapping to a dataset of scientific publications on ocean literacy between 2005 and 2019, obtained from Web of Science and Scopus databases. In order to represent the development of the field, analyze the level of collaborations and uncover its thematic areas, we first used bibliometric analyses to describe the field’s main features, including indicators of growth and research collaboration. We then used science mapping techniques to build collaboration networks among countries and institutions, and to identify research communities. Lastly, we performed co-word analysis to reveal the underlying thematic areas and their evolution. Our results reveal a slow-growing number of publications and a promising trend for collaboration among authors, countries and institutions. Education and science were identified as the two major thematic areas on ocean literacy showing that, over time, issues related to these themes have gained more attention among researchers. These findings confirm that ocean literacy is gaining more acknowledgment within the scientific community but still faces considerable limitations to its dissemination in sectors like the blue economy and in regions such as Latin America and Africa. Promoting cross-institutional and cross-disciplinary cooperation among research institutions, marine education networks and the industry is critical to support this purposeful movement and represents an urgent challenge.

A new probabilistic approach to estimating marine gastropod densities from baited traps - Jennifer Coston‐Guarini; Jean‐Marc Guarini; Frederike Ricarda Boehm; Thomas R. H. Kerkhove; Frances C. Rivera; Karim Erzini; François Charles; Tim Deprez; Laurent Chauvaud (Marine Ecology, 2018)
A new probabilistic approach is proposed to assess muricid species population abundances at scales relevant to both Ancient and Modern coastal fisheries. Motivated by the long‐term goal of reconstructing the dynamics of exploited murex populations during Antiquity, the objective was to estimate the population density of the banded dye‐murex, Hexaplex trunculus (Linnaeus, 1758) from successive captures with baited traps, using a method similar to the technique employed in the Mediterranean purple dye industry. The stochastic model developed simulates cumulative captures while accounting for high variability. It was calibrated with data acquired during a field trapping experiment (Crete Island, Greece). Traps’ catchability and Effective Area of Attraction (EAA) were estimated using the individual speed and behavioural response towards bait from laboratory experiments. Average density of H. trunculus was estimated as 2.2 ± 1.4 SE individuals per square metre, with no significant differences between seagrass and rocky habitats. The clearing time of successive capture experiments averaged 84 ± 6 SE hr. Clearing ca . 0.4 ha of subtidal area would be necessary to produce ca . 1.0 g of pure Tyrian purple pigment. The method described is generalizable to making population abundance estimates for similar groups, such as whelks, in modern fisheries.

Idiomysis mozambicus, a new mysid species (crustacea: mysidacea) from Mozambique - Tim Deprez; Tris Wooldridge; Jan Mees (Hydrobiologia, 2001)

A new species of Gastrosaccus (Crustacea, Mysidacea) from Algoa Bay (South Africa) - Tim Deprez; Tris Wooldridge; Jan Mees (Hydrobiologia, 2000)